Human rhinoviruses in otitis media with effusion - Chantzi, F. M.; Papadopoulos, N. G.; Bairamis, T.; Tsiakou, M.; Bournousouzis, N.; Constantopoulos, A. G.; Liapi, G.; Xatzipsalti, M.; Kafetzis, D. A. (Pediatr Allergy Immunol, 2006)
Frequent viral upper respiratory tract infections (URTI) are considered to be risk factors for otitis media with effusion (OME). Atopy has also been associated with both OME and viral infections. The aim of this study was to evaluate the presence of viruses in middle ear effusions (MEE) in children 2-7 yr old with OME, and to determine risk factors for virus detection in the MEE. MEE samples, collected at the time of myringotomy from 37 children with OME were assessed. Physical examination, skin prick tests and a standardized questionnaire on OME and allergy were also performed. Viral RNA was detected by the use of reverse transcription PCR (RT-PCR). Fifteen samples (40.5%) were positive for rhinovirus (RV). One enterovirus and no other respiratory viruses were detected. Two out of five (40%), 3/7 (43%) and 10/25 (40%) were positive for RV in acute, subacute and chronic cases, respectively. Children with frequent episodes of OM, with early onset of OM (<2 yr old), and a positive family history of allergy had a statistically increased risk of RV detection. The two groups were comparable with respect to all other parameters examined. RV is the predominant virus recovered by RT-PCR in the middle ear cavity of children with asymptomatic OME, especially those with a history of longstanding OME or repeated episodes, or children with a family history of allergy. Interactions between allergy and RV infections are likely to predispose to middle ear disease.
Keywords: Child Child; Preschool Cross-Sectional Studies Enterovirus Female Humans Male Otitis Media with Effusion Picornaviridae Infections Questionnaires RNA; Viral Rhinovirus Risk Factors Skin Tests